An Examination of Factors That Influence Students' IT Career Decisions. Issue 3 (3rd July 2018) - Young, Diana K.; Carpenter, Darrell; Maasberg, Michele
ABSTRACT: A key challenge resulting from the rapid growth of the information technology (IT) industry is finding enough qualified workers to fill available positions. In this paper, Holland's Theory of Occupational Themes, Social Cognitive Career Theory, and Career Construction Theory are used to investigate how job-related beliefs, career planning perceptions, and occupational congruence work together to influence students' career decisions, major satisfaction, and academic performance. Using 210 student responses, we empirically test a theoretically derived research model. Our findings suggest that job security is a strong predictor of both IT career optimism and career planning ability. In addition, career optimism and career planning ability are important antecedents of students' IT career commitment, which significantly influences satisfaction with academic major. A modest portion of academic performance was explained by the model. Most notably, occupational congruence was found to be a poor predictor of academic major satisfaction and performance.